ADMINISTRATIVE REFORM IN BUREAUCRACY AND CIVIL SERVICE: Administrative reform, Bureaucracy reform, Civil Service reform, Developing Countries - admin, admin (JAMAK, 2014)
It is a common for public organization to make kinds of reform in achieving the goals. One of basic reform in public organization is administrative reform. This reform is mainly in institutional and personal matters. In conceptual term, this reform is just an early step for public organization to challenge its target. However, many countries especially in developing countries still struggle in this step. So, it is very fruitful for us to study on administrative reform due to the existing need for public organization in terms of bureaucratic and civil service reforms. This study analyze and criticize the existing of bureaucracy and civil service reform in some developing countries. In seven Arab countries institutional and personal reform is still in a piecemeal approach rather than systemic or integrative approach. Civil service is still lack of having information to cope and implement the reform released. In addition, Indonesia as one of the developing country is also still struggle for its administrative reform in terms of its bureaucracy and civil service. Barriers in salary, institution and regulation is challenging for next administrative reform. Lack of prioritizing policy and information gap between levels of civil service to make a better administrative reform should be solved on a near future. Some significant negative matters are still occurred, but we may need time and awareness to go. Good regime, policy from government leadership is a must. Further quality and quantity of bureaucracy and its civil servant is another good thing should exist. Those will be run well if it covered by culture, values and mentality that cope the need for reform.